The governance of Internet and game theory - Lefebvre, Olivier (International Journal of Engineering and Technology, 2018)
The professional milieu of telecommunications is livened up by controversies lasting decades.Â The controversy about access charges (or termination rates, the price paid by an operator to another when the subscriberâ€™s call ends on its network) is ending, while the controversy about Net neutrality is starting. The article focuses on a â€œfragmentâ€: the regulatorâ€™s action. Game theory is useful to answer two questions: (1) why does the regulator decide the decrease and cancellation of access charges (justification)? (2) How does he do it (tactical feasibility)? When the access charges decrease and are cancelled the retail prices decrease and the consumersâ€™ surplus increases. And concerning the tactical feasibility, the regulator can let untouched the profits when he decides some decrease of the access charges (direct effect), then the retail prices decrease when there is a new Nash equilibrium (strategic effect). The operators cannot protest, neither during the first stage (the profits are untouched) neither during the second stage (it would be to admit that access charges are useful to have higher profits thanks to high retail prices, which is detrimental to consumers).One brings some explanation of the move towards access charges lowered or cancelled. Examples are: (1) the peering in the governance of Internet and (2) what is called the Eurotariff (for instance, roaming charges for users of mobile phones in Europe have been cancelled).Â Â